2021
DOI: 10.1073/pnas.2020057118
|View full text |Cite
|
Sign up to set email alerts
|

DLL1 orchestrates CD8+T cells to induce long-term vascular normalization and tumor regression

Abstract: The immunosuppressive and hypoxic tumor microenvironment (TME) remains a major obstacle to impede cancer immunotherapy. Here, we showed that elevated levels of Delta-like 1 (DLL1) in the breast and lung TME induced long-term tumor vascular normalization to alleviate tumor hypoxia and promoted the accumulation of interferon γ (IFN-γ)–expressing CD8+ T cells and the polarization of M1-like macrophages. Moreover, increased DLL1 levels in the TME sensitized anti-cytotoxic T lymphocyte–associated protein 4 (anti-CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…In turn, this could lead to continued localized seeding of tumors with the generated effector T cells. Inflammatory signals produced by the activated T cells could also lead to further activation of neighboring myeloid and endothelial cells, promoting recruitment of additional resource and effector T cells from the vasculature, which has been observed after both checkpoint blockade and CEA-TCB therapies (57,60,99,(105)(106)(107)(108)(109)(110)(111). Additional chemoattraction and activation of T cells already present in the tumor is also likely (60).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In turn, this could lead to continued localized seeding of tumors with the generated effector T cells. Inflammatory signals produced by the activated T cells could also lead to further activation of neighboring myeloid and endothelial cells, promoting recruitment of additional resource and effector T cells from the vasculature, which has been observed after both checkpoint blockade and CEA-TCB therapies (57,60,99,(105)(106)(107)(108)(109)(110)(111). Additional chemoattraction and activation of T cells already present in the tumor is also likely (60).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, similar to adaptive lymphocytes, innate immune cell localization within the tumor may be a direct reflection of their functional properties, driven by local gradients of nutrients from local vasculature vs. exposure to suppressive factors generated by highly proliferative malignant cells. In this regard, therapies promoting vascular normalization have demonstrated efficacy when combined with immune targeted treatments (106,107,109,(120)(121)(122)(123)(124). Therefore, functional tumor vasculature appears to serve as a major organizational hub for spatially coordinated activities of innate and adaptive immune cells, both through improving local cellular recruitment and allowing normal metabolic and cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous article reported that fibroblasts with somatic copy number alterations in the TME play synergetic roles in tumor development through complex interactions with cancer cells, and RCN3 is identified as a fibroblast-specific biomarker of poorer prognosis of colorectal cancer (CRC) ( 21 ). In contrast, the tumor-infiltrating lymphocytes (TLSs), CD8 + T lymphocytes, play a pivotal role in survival prognosis, tumor regression, and antitumor immunity, through weakening CD8 + T cell activation, immunosuppressive factors in TME maintain tumor immune inhibition status ( 37 39 ). Thus, TAMs and CAFs are potential target cells for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another observation of long-term vascular normalization and antitumor immunity by activated CD8 + T cells, though not an example of immunotherapy causing vascular normalization, adds further support to this positive feedback cycle hypothesis ( Zhang et al, 2021 ). Specifically, researchers studied the ligand Delta-like canonical Notch ligand 1 (DLL1) ( Huang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 86%
“…When DLL1-Notch signaling is reduced in bone marrow precursors by circulating VEGF, T cell activation and antitumor immunity is reduced ( Huang et al, 2011 ). However, interfering with circulating VEGF-induced DLL1-Notch signaling inhibition by overexpressing DLL1 in cancer cells induced long-term vascular normalization ( Zhang et al, 2021 ). This normalization was dependent on IFNγ production and CD8 + T cell accumulation ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%